2000
DOI: 10.1257/aer.90.4.869
|View full text |Cite
|
Sign up to set email alerts
|

A Reassessment of the Relationship Between Inequality and Growth

Abstract: This paper challenges the current belief that income inequality has a negative relationship with economic growth. It uses an improved data set on income inequality which not only reduces measurement error, but also allows estimation via a panel technique. Panel estimation makes it possible to control for time-invariant country-specific effects, therefore eliminating a potential source of omitted-variable bias. Results suggest that in the short and medium term, an increase in a country's level of income inequal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

73
1,122
20
88

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,460 publications
(1,355 citation statements)
references
References 16 publications
73
1,122
20
88
Order By: Relevance
“…4 A review by Benabou (1996:13) …nds that 'These regressions, run over a variety of datasets and periods with many di¤erent measures of income distribution, deliver a consistent message: initial inequality is detrimental to long-run growth. ' In contrast, Forbes (2000) found that in the short and medium term, an increase in a country's level of income inequality has a signi…cant positive relationship with subsequent economic growth. Still other studies have found more nuanced relations between inequality and growth.…”
Section: The Importance Of Inequality Measurementmentioning
confidence: 83%
“…4 A review by Benabou (1996:13) …nds that 'These regressions, run over a variety of datasets and periods with many di¤erent measures of income distribution, deliver a consistent message: initial inequality is detrimental to long-run growth. ' In contrast, Forbes (2000) found that in the short and medium term, an increase in a country's level of income inequality has a signi…cant positive relationship with subsequent economic growth. Still other studies have found more nuanced relations between inequality and growth.…”
Section: The Importance Of Inequality Measurementmentioning
confidence: 83%
“…However, as argued by Forbes (2000), although most of these works focus on the theories establishing a negative effect of inequality on growth, a careful reading of this literature suggests that this negative relationship is far less definitive than is generally believed. In many models, the negative relationship depends on exogenous factors, such as aggregate wealth, political institutions, or the level of development.…”
Section: The Effects Of Economic Inequality: What We Know and What Wementioning
confidence: 99%
“…Moreover, some studies made during this time (Saint-Paul and Verdier 1993;Galor and Tsiddon 1997a;Benabou 1996) found a positive theoretical relationship between inequality and growth. According to Forbes (2000), these papers received less attention because of the empirical negative relationship +reported at the time.…”
Section: The Effects Of Economic Inequality: What We Know and What Wementioning
confidence: 99%
See 2 more Smart Citations